Contribution of Intermediate and High Trophic Level Species to Benthic-Pelagic Coupling: Insights From Modelling Analysis - Ricci, Pasquale; Carlucci, Roberto; Capezzuto, Francesca; Carluccio, Angela; Cipriano, Giulia; D’Onghia, Gianfranco; Maiorano, Porzia; Sion, Letizia; Tursi, Angelo; Libralato, Simone (Frontiers in Marine Science, 2022)
Benthic-pelagic coupling (BPC) is a combination of downward (from pelagic to benthic) and upward (from benthic to pelagic) flows of organic matter and nutrients mediated by trophic interactions in the food web. Hydrological changes in marine ecosystems affect BPC patterns at several temporal and spatial scales. Thus, a food-web perspective help to to quantify and disentangle the role of ecosystem components and high trophic levels species in the BPC. This study investigated the spatio-temporal variability of energy and matter flows between the benthic and pelagic domains in two areas (Salento and Calabria) of the Northern Ionian Sea (Central Mediterranean Sea) during two different periods. The region is subject to large-scale oceanographic changes, e.g., the Adriatic-Ionian Bimodal Oscillating Systems (BiOS), that might result in relevant spatial and temporal BPC changes. Four food-web models describe the trophic structure, the role of ecosystem components and energy flows in the Salento and Calabrian areas, during two BiOS periods, the anticyclonic (1995-1997) and the cyclonic phases (2003-2005). The food webs are described by 58 functional groups obtained by aggregating species into ecological domains, depth gradients and biological traits. The role of species in the BPC has been quantified using a new Benthic-Pelagic Coupling Index calculated on the basis of food web flows estimated by models. The results highlight the pivotal role of deep faunal communities, in which demersal and benthopelagic species sustain upward energy flows towards the pelagic domain and shelf faunal communities. Temporal changes driven by BiOS affect the trophic state of the deep communities resulting in considerable variations in their amount of consumption flows. In addition, the presence of submarine canyons seems to better support the stability of the Calabrian food web in both investigated periods, whereas geomorphological traits of the Salento area seem to support greater pelagic production during the cyclonic period than the anticyclonic one. Benthopelagic species show an important role as couplers. In particular, Aristaemorpha foliacea, Hoplostetus mediterraneus, Macrourids and Plesionika martia are important couplers of bathyal communities in both areas.